E-learning quality and satisfaction of user - Utomo, Satrio Matin; Alamsyah, Doni Purnama; Othman, Norfaridatul Akmaliah; Setyawati, Irma; Rohaeni, Heni (2023)
This study examines student satisfaction with using the e-learning concept. Other variables tested include user attitude, e-learning quality, and confirmation. This research will be carried out in 2022, with the object of study being students who use the e-learning concept. This study focuses on online behavior with a research method used by surveys of students. The type of data used for this research method is quantitative, so that the questionnaires distributed to students have answers in the form of numbers. Questionnaires were distributed to students online with a target of 500 respondents. Data from respondents were processed using the SmartPLS statistical tool, the results of the analysis were evaluated based on the research hypothesis. The results show that not all factors support the e- learning satisfaction of students. Only e-learning quality can increase student satisfaction. Meanwhile, the student's attitude and confirmation were unable to keep them properly. This study provides an overview of the importance of e-learning quality when it is associated with user satisfaction with the concept of e- learning at universities.